Seismic assessment of masonry “Gaioleiros” buildings in Lisbon, Portugal - Mendes, N. (2010)
This paper presents a numerical study for the seismic assessment of a Portuguese building masonry typology - “Gaioleiro”. Numerical analysis was performed using a finite element model calibrated with experimental results obtained in 1:3 reduced scale tests carried out in the LNEC 3D shaking table. Non-linear dynamic analysis with time integration and pushover analysis are carried out. Using nonlinear dynamic analysis it was verified that the buildings of “gaioleiro” type with appropriate floor-wall connections are in the limit of their loading capacity. The pushover analyses performed in this study were incapable of simulating correctly the damage of the structure under seismic action.